Using KWL (Know Want Learn) Reading Strategy to Teach Reading Comprehension: A Case in One Public Senior High School in Palembang - Leni Rohliah; Hilma Suryani (Edukasi, 2020)
KWL reading strategy is one of the strategies to improve the ability of comprehending reading text, especially expository texts. The study was conducted to find out whether or not there was a significant difference in the students’ reading achievement in comprehending expository texts between the students who were taught by using KWL Reading Strategy and those who were not. It used one of the quasi-experimental designs--pretest-posttest non-equivalent control group design. There were 79 students of SMA N 4 Palembang participating in this study. In selecting the sample, purposive sampling technique was used. The data were gathered through the use of reading comprehension test. T-test analyses namely paired sample t-test and independent sample test were applied to examine the hypotheses. The results of t-test revealed that there was significant improvement in students’ reading comprehension after the intervention. KWL reading strategies helped students to comprehend the expository text and gave a positive influence to the students’ improvement. Furthermore, teachers could apply this strategy as a variation in teaching reading in his/her class to avoid students’ boredom.